Gold and Biocatalysis for the Stereodivergent Synthesis of Nor(pseudo)ephedrine Derivatives: Cascade Design Toward Amino Alcohols, Diols, and Diamines. Issue 7 (29th March 2023) - González‐Granda, Sergio; Steinkellner, Georg; Gruber, Karl; Lavandera, Iván; Gotor‐Fernández, Vicente
Abstract: The combination of gold(I) and enzyme catalysis has provided access to a series of nor(pseudo)ephedrine derivatives in a regio‐ and stereoselective manner. The approach involves developing IPrAuNTf2 ‐catalyzed hydration of 1‐phenylprop‐2‐yn‐1‐yl acetate or N ‐(1‐phenylprop‐2‐yn‐1‐yl)acetamide, followed by (dynamic) asymmetric biotransamination or bioreduction of the corresponding keto ester or keto amide intermediates. Enzyme actions were completely selective towards the modification of the methyl ketones in a highly stereoselective manner, allowing the synthesis of enantio‐ and diastereomerically enriched products using either racemic or optically active starting materials. Thus, a series of amino alcohol, diol, and diamine derivatives were produced from propargyl esters or amides (57 to 86% isolated yield), the biocatalyst of choice determining the (stereo)selectivity of the overall cascade process (70–99% diastereomeric excess and >98% enantiomeric excess), and providing access to nor(pseudo)ephedrine compounds in a straightforward manner. Abstract :